The Impact of COVID-19 on Financial Markets and the Real Economy - Gherghina, Ştefan Cristian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint comprises 17 papers published in the Special Issue entitled "The Impact of COVID-19 on Financial Markets and the Real Economy", centered on socioeconomic models affected by the pandemic (Vasin, 2022); the COVID-19 impact on various sectors or the economy as a whole, for instance in Canada (Singh et al., 2022), China (Habibi et al., 2022), Slovakia (Svabova et al., 2022), the United States (Rodousakis & Soklis, 2022) or Vietnam (Huynh et al., 2021; Nguyen et al., 2022); the benefits of teleworking on the continuity of operations across various sectors (Santos et al., 2022); research of the tourism and recreational possibilities of Russia and Kazakhstan's cross-border regions and the threats these areas faced during the pandemic (Tanina et al., 2022), the impact of the new coronavirus infection on the Russian labor market (Rodionov et al., 2022); the factors driving young Vietnamese people's intention to use financial technology in the context of the COVID-19 outbreak (Khuong et al., 2022) or those influencing access to credit for informal labor sector (Vu and Ho, 2022); predicting and analyzing Jordanian insurance firms' performance (Altarawneh et al., 2022) or developing an early warning system for solvency risk in the banking industry (Hidayat et al., 2022) during the COVID-19 pandemic; the impact of the pandemic on European stock markets (Keliuotyte-Staniuleniene and Kviklis, 2022); the drivers of cross-border mergers and acquisitions during the pandemic (Lee et al., 2021); examining the financial and fiscal variables of Ecuadorian economic groups (Tulcanaza-Prieto and Morocho-Cayamcela, 2021).